Arabidopsis OXIDATIVE STRESS 3 enhances stress tolerance in Schizosaccharomyces pombe by promoting histone subunit replacement that upregulates drug-resistant genes. Issue 3 (16th September 2021) - Lai, Dingwang; Huang, Xiuting; Wang, Changhu; Ow, David W
Abstract: Histone replacement in chromatin-remodeling plays an important role in eukaryotic gene expression. New histone variants replacing their canonical counterparts often lead to a change in transcription, including responses to stresses caused by temperature, drought, salinity, and heavy metals. In this study, we describe a chromatin-remodeling process triggered by eviction of Rad3/Tel1-phosphorylated H2Aα, in which a heterologous plant protein AtOXS3 can subsequently bind fission yeast HA2.Z and Swc2, a component of the SWR1 complex, to facilitate replacement of H2Aα with H2A.Z. The histone replacement increases occupancy of the oxidative stress-responsive transcription factor Pap1 at the promoters of at least three drug-resistant genes, which enhances their transcription and hence primes the cell for higher stress tolerance.